2021
DOI: 10.1007/s40544-021-0513-5
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a biomimetic robust bi-layered hydrophilic lubrication coating on surface of silicone elastomer

Abstract: Silicone elastomers-based materials have been extensively involved in the field of biomedical devices, while their use is extremely restricted due to the poor surface lubricity and inherent hydrophobicity. This paper describes a novel strategy for generating a robust layered soft matter lubrication coating on the surface of the polydimethylsiloxane (PDMS) silicone elastomer, by entangling thick polyzwitterionic polyelectrolyte brush of poly (sulfobetaine methacrylate) (PSBMA) into the sub-surface of the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…Hydrogels modified with surface polymer molecular brushes are mainly prepared by atom transfer radical polymerization (ATRP), ,,,, activators regenerated by electron transfer for ATRP (ARGET-ATRP), , or photoinduced electron/energy transfer-RAFT (PET-RAFT) polymerization . The surface modification strategies consist of “grafting onto” and “grafting from”.…”
Section: Hydrogel Modified By Surface Polymer Brushesmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogels modified with surface polymer molecular brushes are mainly prepared by atom transfer radical polymerization (ATRP), ,,,, activators regenerated by electron transfer for ATRP (ARGET-ATRP), , or photoinduced electron/energy transfer-RAFT (PET-RAFT) polymerization . The surface modification strategies consist of “grafting onto” and “grafting from”.…”
Section: Hydrogel Modified By Surface Polymer Brushesmentioning
confidence: 99%
“…Hydrogels are promising for a broad range of applications given their outstanding properties of swellability, toughness, flexibility, elasticity, viscoelasticity, fatigue resistance, diffusivity, antifouling, and biomimetic environment. Hydrogel materials with different structures have been designed to implement variable functions, and they have been extensively employed in cell culture, , drug delivery, tissue scaffolds, wound dressings, antifouling materials, contact lenses, , sensors, flexible and wearable sensing electronics, lubricating material, anti-icing, optical devices, , batteries, , and soft robotics. ,, The chemical composition and the spatial topology of hydrogels determine their properties and functions, which are pivotal for practical applications. The polymer chain of hydrogel with identical compositions can be accommodated in the local environment in various topologies, ranging from linear form to grafted, blocky, star-shaped, bottlebrush, and other complex architectures .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fe 3+ induced tridentate metal coordination with the -COOH group in P(AAm-co-AAc) network and act as the second network to enhance the mechanical property. Inspired by this method, Gao et al fabricated a biomimetic bi-layered coating on the surface of polydimethylsiloxane, which was composed of a robust P(AAm-co-AAc)-Fe 3+ hydrogel substrate and an entangling polyzwitterionic polyelectrolyte brush layer on the top surface (Figure 5b) [87]. The COF of the coating could remain low friction (COF <0.05) stably during the friction test of 50,000 sliding cycles under 10 N load, exhibiting excellent anti-wear property.…”
Section: Dual-cross-linked Hydrogelmentioning
confidence: 99%
“…As for lubricating coating design, natural synovial joints provided an excellent paradigm. Natural joints exhibited extremely efficient lubrication with coefficients of friction (COF) <0.01 under a wide range of contact loads. , The ultralow COF of joints resulted from the hydration lubrication mechanism of charged biomacromolecules on the cartilage surface, which can tightly bound large amounts of water molecules to form a tenacious but fluid-like hydration layer. , Inspired by joint lubrication, a variety of hydrophilic polymer coatings have been explored as promising boundary lubrication layers to reduce the interface friction of bioimplant surfaces. Charged polymers, especially zwitterionic poly­(2-methacryloyloxyethyl phosphorylcholine) (PMPC), were recognized as the most optimal materials for hydration lubrication. Recently, Xu et al developed a low friction, nonirritating, and anti-inflammatory hyaluronic acid-based coating on the tracheal tube. The study in animal models demonstrated that the multifunctional coating could effectively relieve the complications of endotracheal intubation. , In addition, Liu et al.…”
Section: Introductionmentioning
confidence: 99%